Glass fiber compositions and glass fibers and composites thereof with low dielectric properties

TW202637500AActive Publication Date: 2026-09-16JUSHI GRP CO
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
TW114118915
Authority / Receiving Office
TW · TW
Patent Type
Applications
Current Assignee / Owner
Priority Date
2025-02-28
Filing Date
2025-05-20
Publication Date
2026-09-16
Estimated Expiration
2045-05-19

AI Technical Summary

Technical Problem

Existing glass fiber compositions, such as E-glass and D-glass, fail to meet the high-frequency and high-speed requirements of fifth-generation and sixth-generation communication due to high dielectric loss and difficulty in mass production, with D-glass being particularly challenging to melt and clarify.

Method used

A glass fiber composition with controlled SiO2, B2O3, Al2O3, CaO, MgO, ZnO, and La2O3 content, along with balanced ZnO/(CaO+MgO) and La2O3/ZnO ratios, to achieve low dielectric constant and loss, improved melting and forming temperatures, and reduced crystallization and phase separation.

Benefits of technology

The composition achieves a dielectric constant ≤ 4.5 and dielectric loss ≤ 2.7‰ at 10GHz, facilitating large-scale production with enhanced forming efficiency and stability.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

A glass fiber composition and glass fibers and composite materials made therefrom with low dielectric properties are disclosed. The glass fiber composition comprises the following components by weight percentage: SiO2 48-57%, B2O3 19-29%, Al2O3 10-14%, CaO 0.5-5.0%, MgO 0-2.0%, ZnO 0.5-6.0%, La2O3 0.05-4.0%, Na2O+K2O+Li2O total 0.01-0.45%, and Fe2O3 0-0.5%. The total weight percentage of each component is greater than or equal to 99.0%, the weight percentage ratio C1 = ZnO / (CaO+MgO) ranges from 0.25 to 2.5, and the weight percentage ratio C2 = La2O3 / ZnO ranges from 0.008 to 4. Using this glass fiber composition, glass fibers with low dielectric constant, low dielectric loss, moderate viscosity, and a wide fiber forming range can be obtained.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] This application relates to a glass fiber composition and glass fibers and composite materials made from the composition, particularly to glass fibers with high frequency and low dielectric properties, which are especially suitable for the fields of copper clad laminates and printed circuit boards. [Previous Technology]

[0002] The "14th Five-Year Plan for National Economic and Social Development and the Outline of Long-Term Goals for 2035" released by the State Council at the end of 2020 clearly pointed out: Systematically plan new infrastructure and accelerate the construction of fifth-generation mobile communication, industrial internet, and big data centers. With the arrival of the highly information-driven era, electronic device development has entered a new stage of high integration and lightweighting, further expanding the demand for copper-clad laminates (CCL) and printed circuit boards (PCBs). Low-dielectric glass fiber, as an important component of electronic glass fiber cloth, CCL, and PCB, has a promising market prospect due to meeting the high-frequency and high-speed parameter requirements of fifth-generation and sixth-generation communication. Its core performance characteristics are low dielectric constant and low dielectric loss, and the lower the better. However, traditional electronic glass (alkali-free glass, abbreviated as E glass) cannot meet the needs of high-end CCL and PCB.

[0003] Against this backdrop, researchers both domestically and internationally have been continuously developing in this field. However, existing research findings often have some shortcomings in practical applications. It is well known that quartz glass possesses excellent low dielectric properties, with a dielectric constant of approximately 3.74 and a loss of approximately 0.2‰ at a high frequency of 10GHz, essentially representing the low-loss limit for glass materials. However, its melting and drawing requirements are too high, making mass production difficult. Therefore, D-glass was developed. Its main composition is a SiO2+B2O3 system, with an electrical constant below 4.5 and excellent dielectric loss performance. However, D-glass also has significant drawbacks; it remains difficult to melt and clarify, hindering fiber drawing and shaping. In existing patented technologies, the glass composition system is basically Si2O+B2O3+Al2O3+CaO+MgO. Its dielectric constant is ≤4.8 and dielectric loss is ≤4.0‰ under high frequency conditions of 10GHz. The high temperature viscosity and forming range of the glass are moderate. However, although it has the feasibility of continuous production, it is difficult to break through the dielectric loss to below 2.5‰ under the condition of ensuring production requirements.

[0004] As a result, related technologies were developed.

[0005] In patent CN118176170A, the quality content of each component is as follows: SiO2 is 36~48%, B2O3 is 18~32%, Al2O3 is 12~24%, P-2O5 is 2.5~8.9%, and CaO+MgO is 5.0~13.0%.

[0006] In patent CN116670091A, the quality content of each component is as follows: SiO2 is 50~61%, B2O3 is 16~27%, Al2O3 is 7~14%, P2O5 is 0.2~4.0%, TiO2 is 0.5~5%, CaO is 0.1~5.0%, MgO is 0~4.0%, and F2+Cl2 is 0~2.0%.

[0007] In patent CN103482876A, the quality content of each component is as follows: SiO2 is 48%~53%, Al2O3 is 13%~16%, B2O3 is 19%~25%, P2O5 is 0.5%~2%, CaO is 5.0%~8.5%, La2O3 is 0.5%~8%, ZnO is 0.5%~2.5%, TiO2 is 0.5%~2%, Na2O, K2O and Li2O are less than 1%, SO3 is less than 0.45%, and Fe2O3 is less than 0.45%. [Summary of the Invention]

[0008] In view of the shortcomings of existing low dielectric glass fiber technology, and in combination with the characteristics of glass fiber production process, this application provides a glass fiber composition and glass fibers with low dielectric properties made therefrom. The glass fiber composition can produce glass fibers with low dielectric constant, low dielectric loss, moderate viscosity and wide fiber forming range.

[0009] To achieve the above objectives, this application controls the contents of SiO2, B2O3, Al2O3, CaO, and MgO, selectively introduces low contents of alkali metal oxides, introduces appropriate amounts of ZnO and La2O3, and rationally sets the range of ZnO / (CaO+MgO) and La2O3 / ZnO ratios. These measures not only achieve lower glass dielectric constant and dielectric loss under 10GHz high-frequency conditions, but also improve the glass melting and forming temperature, reduce the tendency of glass crystallization and phase separation, and are beneficial to improving the forming efficiency of glass fibers. Compared with quartz glass and D glass, this application greatly reduces the production difficulty while ensuring dielectric properties, has excellent comprehensive performance, and is more practical.

[0010] The specific technical solution adopted in this application is as follows:

[0011] This application provides a glass fiber composition and a glass fiber with low dielectric properties made therefrom. The glass fiber composition comprises the following components, the content of each component being expressed as a weight percentage: SiO2 48~57%, B2O3 19~29%, Al2O3 10~14%, CaO 0.5~5.0%, MgO 0~2.0%, ZnO 0.5~6.0%, La2O3 0.05~4.0%, the total amount of Na2O+K2O+Li2O 0.01~0.45%, and Fe2O3 0~0.5%. The sum of the weight percentages of all components is greater than or equal to 99.0%, the weight percentage ratio C1 = ZnO / (CaO+MgO), the value of C1 is 0.25~2.5, and the weight percentage ratio C2 = La2O3 / ZnO, the value of C2 is 0.008~4.

[0012] In a glass network, the glass dielectric generates induced charges when an external electric field is applied, weakening the electric field. The ratio of the original applied electric field to the final electric field in the dielectric is the dielectric constant. When the glass dielectric is suddenly subjected to an electric field, it often takes a period of time for the polarization to reach its final value, resulting in energy loss. This phenomenon is called structural relaxation. Therefore, the essential characteristics of the glass dielectric constant and dielectric loss are the dielectric polarization and structural relaxation of the glass.

[0013] Based on the general CaO-B2O3-SiO2-Al2O3 glass system, this application controls the content of MgO and alkali metals, and simultaneously introduces ZnO and La2O3, rationally setting the ratio of ZnO to CaO, MgO, and La2O3 to ZnO, while ensuring the amount of Al2O3 and SiO2. By controlling the dielectric polarization and structural relaxation of the glass network, the melting and molding temperature of the glass is improved while ensuring the dielectric properties of the glass, and the tendency of the glass to crystallize and separate phases is reduced. Here, crystallization of glass refers to the precipitation of crystals in amorphous glass, while phase separation refers to the formation of two or more amorphous states in a homogeneous amorphous glass, causing inhomogeneity. Apparently, both crystallization and phase separation will cause the glass to devitrify, and these devitrification behaviors will have an adverse effect on the forming of glass fibers, hindering the continuous drawing of glass fibers.

[0014] SiO2 is the main oxide forming the glass skeleton and plays a role in stabilizing the components. In order to obtain better glass dielectric properties and melting effect, this application prefers that the SiO2 content not be too high. If the SiO2 content is too high, although some dielectric properties can be guaranteed, the viscosity of the glass will be too high, making glass fiber production difficult. Conversely, the SiO2 content should not be too low. If the SiO2 content is too low, the skeleton effect of the glass network will be reduced, which is detrimental to the dielectric properties of the glass. Therefore, in the glass fiber composition of this application, the weight percentage content of SiO2 is limited to 48-57%, preferably 48-56%, and more preferably 48-54%.

[0015] B2O3 is also a major oxide forming the glass skeleton. Compared to SiO2, B2O3 is more conducive to melting, but when its content is too high, the glass is prone to instability, leading to phase separation. Phase separation affects the drawing performance of glass fibers. The essence of this phase separation is the competition between B and Si, two glass-forming elements, for oxygen ion groups. The optimal combination is the balance between the two. Therefore, in the glass fiber composition of this application, the weight percentage content of B2O3 is limited to 19-29%, preferably 19.5-27%, and more preferably 21-26%.

[0016] Al₂O₃ is an intermediate oxide that plays an important role in preventing phase separation in glass. It is generally believed that glass is prone to phase separation when the alumina content is below 10%, but excessively high content leads to high viscosity. Therefore, in the glass fiber composition of this application, the weight percentage content of Al₂O₃ is limited to 10-14%. In some embodiments, it is 10-13%.

[0017] CaO and MgO are alkaline earth metal oxides, which can lower the melting temperature of glass, with CaO having a more pronounced effect. To ensure the dielectric properties and melting process of the glass, this application limits the weight percentage content of CaO to 0.5-5.0% and the MgO content to 0-2.0%. Preferably, the weight percentage content of CaO is 0.9-4.0%, more preferably 2.0-4.0%. In some embodiments, the weight percentage content of MgO is 0-1.5%. In some embodiments, the glass fiber composition of this application does not contain MgO.

[0018] In glass networks, ZnO typically uses zinc-oxygen octahedrons as the outer oxide of the network. When there is sufficient free oxygen in the glass, zinc-oxygen tetrahedra can form and enter the glass's structural network, making the glass structure more stable. Generally, the ZnO content in glass does not exceed 5% to 6%, as excessive ZnO will make the glass prone to crystallization. In addition, ZnO can lower the melting temperature of glass. Therefore, in the glass fiber composition of this application, the weight percentage content of ZnO is limited to 0.5% to 6.0%, preferably 1.5% to 6.0%, more preferably 1.5% to 5.5%, and even more preferably 2% to 5%.

[0019] To ensure the dielectric and production performance of the glass fiber in this application, the weight percentage ratio C1 is limited to ZnO / (CaO+MgO), and the value of C1 is controlled between 0.25 and 2.5. If the value of C1 is too high, the influence of ZnO will be greater than that of CaO+MgO, leading to phase separation or crystallization of the glass, and it will also be detrimental to the dielectric performance. Here, Zn, Ca, and Mg atoms all exhibit a +2 valence, but Zn is different from Ca and Mg; its polarization ability is not as strong as that of Ca and Mg. The dielectric performance and devitrification behavior of the glass network system need to be controlled, and C1 is a direct manifestation of this control result. If the value of C1 is too low, the effect of ZnO will be insignificant, the structural stability of the glass will decrease, and thus affect the overall performance of the glass. Preferably, the value of C1 is between 0.25 and 2.3.

[0020] Rare earth oxide La2O3 is rarely introduced into electronic-grade glass fiber technology. Experiments have shown that introducing La2O3 into the glass fiber composition of this application, and limiting the weight percentage content of La2O3 to 0.05-4.0%, results in superior dielectric and melting properties of the glass. However, excessively high La2O3 content can negatively impact the dielectric properties of the glass. Therefore, the La2O3 content is limited to 0.05-4.0%. In some embodiments, the La2O3 content is 0.05-3.5%. In some embodiments, the La2O3 content is 1.3-4.0%.

[0021] To further ensure the dielectric and manufacturing performance of this application, the weight percentage ratio C2 = La2O3 / ZnO is limited to 0.008~4. When the value of C2 is too high, the effect of La2O3 will overshadow ZnO, and the overall synergistic effect of the two will be reduced, leading to deviation in dielectric performance; when the value of C2 is too low, the effect of La2O3 is not obvious, and the ability to control phase separation and crystallization will be reduced. Preferably, the value of C2 is 0.008~2, more preferably 0.008~1.5.

[0022] In the glass industry, alkali metal oxides or alkaline earth metal oxides are commonly used as inductors in the network outer layer. However, in electronic-grade glass fibers, excessive amounts of alkali metal oxides or alkaline earth metal oxides can reduce the electrical insulation and dielectric properties of the glass, while excessively low amounts can lead to excessively high viscosity. Therefore, in the glass fiber composition of this application, the total weight percentage of alkali metals Na₂O + K₂O + Li₂O is limited to 0.01~0.45%, preferably 0.01~0.30%, and more preferably 0.01~0.25%. In some embodiments, the total weight percentage of Na₂O + K₂O + Li₂O is 0.01~0.20%.

[0023] Fe2O3 is beneficial for glass melting and improves the crystallization properties of glass. Excessive content can affect the dielectric properties of glass fibers and also corrode the platinum materials in the furnace. In the glass fiber composition of this application, the weight percentage content of Fe2O3 is limited to 0-0.5%, preferably 0-0.3%. In some embodiments, the glass fiber composition of this application does not contain Fe2O3.

[0024] In this application, the total weight percentage of the main components of the glass fiber composition, namely SiO2, B2O3, Al2O3, CaO, MgO, ZnO, La2O3, Na2O, K2O, Li2O, and Fe2O3, is greater than or equal to 99.0%, preferably greater than or equal to 99.2%, and even more preferably greater than or equal to 99.5%.

[0025] Based on the main scheme, this application may also introduce an appropriate amount of F2. Extensive experiments have shown that an appropriate amount of F2 can play a significant role in fluxing, reducing molding temperature and liquidus temperature, and is easily removed during waste gas treatment. Experiments have found that the presence of an appropriate amount of F2 in glass is beneficial for reducing the dielectric constant of the glass. Therefore, an appropriate amount of F2 may be introduced into the glass fiber composition of this application. When introducing F2, the weight percentage content of F2 is limited to 0~1.6%, preferably 0~1.5%, and more preferably 0~0.5%.

[0026] The glass fiber composition of this application may also contain TiO2. TiO2 has a certain fluxing effect, but if the content is too high, it will cause the glass fiber to exhibit ion coloring, affecting the application of low dielectric glass fiber. Therefore, in the glass fiber composition of this application, the weight percentage content of TiO2 is limited to 0~0.4%, preferably 0~0.3%. In some embodiments, the glass fiber composition of this application does not contain TiO2.

[0027] In some embodiments, when the glass fiber composition of this application incorporates 0-0.4% TiO2 and / or 0-1.6% F2, the total weight percentage of each component, i.e., the total weight percentage of SiO2, B2O3, Al2O3, CaO, MgO, ZnO, La2O3, Na2O, K2O, Li2O, Fe2O3, TiO2, and F2, is greater than or equal to 99.3%; in some embodiments, it is greater than or equal to 99.5%; and in some embodiments, it is greater than or equal to 99.8%.

[0028] In order to control production costs, glass density and improve environmental protection, the glass fiber composition of this application does not contain P2O5.

[0029] According to another aspect of this application, a glass fiber with low dielectric properties is provided, the glass fiber with low dielectric properties being made from the above-mentioned glass fiber composition, specifically, the glass fiber with low dielectric properties being made from the above-mentioned glass fiber composition by conventional methods.

[0030] The glass fiber according to this application has a dielectric constant ≤ 4.5 and a dielectric loss ≤ 2.7‰ at 10GHz. In some embodiments, the dielectric constant ≤ 4.4 and the dielectric loss ≤ 2.2‰.

[0031] For low-dielectric glass fibers, the molding temperature is generally required to be between 1200-1400℃, preferably controlled between 1290℃ and 1380℃. Excessively high temperatures require matching furnace processes. The molding range ΔT is generally required to exceed 50℃, the larger the better; under specific processes, ΔT can be controlled above 30℃. In some embodiments, the glass fiber according to this application has a molding temperature between 1335-1380℃ and a ΔT range of 37-148℃. In some embodiments, the molding temperature is between 1349-1375℃ and the ΔT range is 60-125℃.

[0032] According to a third aspect of this application, a composite material is provided, the composite material comprising the glass fiber described above.

[0033] Compared with the prior art, this application introduces appropriate amounts of ZnO and La2O3, controls the MgO content, and ensures the dosage of Al2O3, SiO2, and B2O3, while introducing low amounts of alkali metal oxides and selectively introducing fluorine. Based on a reasonable setting of the content of each component, the proportions of ZnO to CaO, MgO, and La2O3 to ZnO are also rationally determined. These measures not only control the polarization and relaxation of the glass network, resulting in a lower glass dielectric constant and lower glass dielectric loss, but also improve the glass melting and forming temperature, reduce the tendency of glass crystallization and phase separation, and are beneficial to improving the forming efficiency of glass fibers. Compared with traditional E glass, this application has a lower dielectric constant and dielectric loss; compared with traditional D glass, this application has a better melting effect and is more suitable for large-scale tank furnace production.

Implementation Method

[0034] To make the objectives, technical solutions, and advantages of the embodiments of this application clearer, the technical solutions in the embodiments of this application will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of this application, not all embodiments. Based on the embodiments in this application, all other embodiments obtained by those skilled in the art without making progressive efforts are within the scope of protection of this application. It should be noted that, unless otherwise specified, the embodiments and features in the embodiments of this application can be arbitrarily combined with each other.

[0035] In this application, the glass fiber composition comprises the following components, the content of each component being expressed as a weight percentage: SiO2 48~57%, B2O3 19~29%, Al2O3 10~14%, CaO 0.5~5.0%, MgO 0~2.0%, ZnO 0.5~6.0%, La2O3 0.05~4.0%, the total amount of Na2O+K2O+Li2O 0.01~0.45%, and Fe2O3 0~0.5%. The sum of the weight percentages of all components is greater than or equal to 99.0%, the weight percentage ratio C1 = ZnO / (CaO+MgO), the value of C1 is 0.25~2.5, and the weight percentage ratio C2 = La2O3 / ZnO, the value of C2 is 0.008~4. The glass fiber composition may also contain 0 to 0.4% TiO2 by weight and 0 to 1.6% F2 by weight.

[0036] The following are examples of preferred value ranges for each component of the glass fiber composition according to this application.

[0037] Preferred Example 1

[0038] The glass fiber composition according to this application contains the following components, the content of each component being expressed as a weight percentage: SiO2 48~56%, B2O3 19.5~27%, Al2O3 10~14%, CaO 0.9~5.0%, MgO 0~2.0%, ZnO 1.5~6.0%, La2O3 0.05~3.5%, Na2O+K2O+Li2O 0.01~0.45%, Fe2O3 0~0.5%, TiO2 0~0.4%, F2 0~1.5%;

[0039] Wherein, the sum of the weight percentages of the above components is greater than or equal to 99.3%, the weight percentage ratio C1 = ZnO / (CaO+MgO), the range of C1 is 0.25~2.5, the weight percentage ratio C2 = La2O3 / ZnO, the range of C2 is 0.008~2; the glass fiber composition does not contain P2O5.

[0040] Preferred Example 2

[0041] The glass fiber composition according to this application contains the following components, the content of each component being expressed as a weight percentage: SiO2 48~56%, B2O3 19.5~27%, Al2O3 10~14%, CaO 0.9~5.0%, MgO 0~2.0%, ZnO 1.5~6.0%, La2O3 0.05~3.5%, Na2O+K2O+Li2O 0.01~0.30%, Fe2O3 0~0.5%, TiO2 0~0.3%;

[0042] The total weight percentage of the above components is greater than or equal to 99.3%, the weight percentage ratio C1=ZnO / (CaO+MgO), the range of C1 is 0.25~2.5, and the weight percentage ratio C2=La2O3 / ZnO, the range of C2 is 0.008~2.

[0043] Preferred Example 3

[0044] The glass fiber composition according to this application contains the following components, the content of each component being expressed as a weight percentage: SiO2 48~54%, B2O3 19.5~27%, Al2O3 10~14%, CaO 2.0~4.0%, MgO 0~2.0%, ZnO 1.5~6.0%, La2O3 0.05~3.5%, Na2O+K2O+Li2O 0.01~0.30%, Fe2O3 0~0.5%, TiO2 0~0.4%, F2 0~1.5%;

[0045] The total weight percentage of the above components is greater than or equal to 99.5%, the weight percentage ratio C1=ZnO / (CaO+MgO), the range of C1 is 0.25~2.5, and the weight percentage ratio C2=La2O3 / ZnO, the range of C2 is 0.008~2.

[0046] Preferred Example 4

[0047] The glass fiber composition according to this application contains the following components, the contents of each component being expressed as a weight percentage: SiO2 48~54%, B2O3 19.5~27%, Al2O3 10~14%, CaO 2.0~4.0%, MgO 0~2.0%, ZnO 1.5~5.3%, La2O3 0.05~3.5%, Na2O+K2O+Li2O 0.01~0.30%, Fe2O3 0~0.5%, TiO2 0~0.4%;

[0048] The total weight percentage of the above components is greater than or equal to 99.5%, the weight percentage ratio C1=ZnO / (CaO+MgO), the range of C1 is 0.25~2.5, and the weight percentage ratio C2=La2O3 / ZnO, the range of C2 is 0.008~2.

[0049] Preferred Example 5

[0050] The glass fiber composition according to this application contains the following components. The content of each component is expressed as a weight percentage: SiO2 48~56%, B2O3 21~26%, Al2O3 10~14%, CaO 2.0~4.0%, MgO 0~2.0%, ZnO 2.0~5.0%, La2O3 1.3~4.0%, Na2O+K2O+Li2O 0.01~0.20%, Fe2O3 0~0.5%, TiO2 0~0.3%, F2 0~0.5%;

[0051] The weight percentage ratio C1 = ZnO / (CaO+MgO), the range of C1 is 0.25~2.5, and the weight percentage ratio C2 = La2O3 / ZnO, the range of C2 is 0.008~2.

[0052] Preferred Example 6

[0053] The glass fiber composition according to this application contains the following components, the content of each component being expressed as a weight percentage: SiO2 48~54%, B2O3 21~26%, Al2O3 10~14%, CaO 2.0~4.0%, MgO 0~1.5%, ZnO 2~5%, La2O3 0.05~3.5%, Na2O+K2O+Li2O 0.01~0.20%, Fe2O3 0~0.5%, TiO2 0~0.4%, F2 0~0.5%;

[0054] The total weight percentage of the above components is greater than or equal to 99.5%, the weight percentage ratio C1=ZnO / (CaO+MgO), the range of C1 is 0.25~2.3, and the weight percentage ratio C2=La2O3 / ZnO, the range of C2 is 0.008~1.5.

[0055] Preferred Example 7

[0056] The glass fiber composition according to this application contains the following components, the content of each component being expressed as a weight percentage: SiO2 48~54%, B2O3 19.5~27%, Al2O3 10~14%, CaO 2.0~4.0%, MgO 0~2.0%, ZnO 1.5~6.0%, La2O3 0.05~3.5%, Na2O+K2O+Li2O 0.01~0.45%, Fe2O3 0~0.3%, TiO2 0~0.4%;

[0057] The total weight percentage of the above components is greater than or equal to 99.8%, the weight percentage ratio C1=ZnO / (CaO+MgO), the range of C1 is 0.25~2.5, and the weight percentage ratio C2=La2O3 / ZnO, the range of C2 is 0.008~2.

[0058] Preferred Example 8

[0059] The glass fiber composition according to this application contains the following components, the content of each component being expressed as a weight percentage: SiO2 48~57% B2O3 19~29% Al2O3 10~14% CaO 0.5~5.0% MgO 0~2.0% ZnO 0.5~6.0% La2O3 0.05~4.0% Na2O+K2O+Li2O 0.01~0.45% Fe2O3 0~0.5%;

[0060] Wherein, the sum of the weight percentages of the above components is greater than or equal to 99.0%; the weight percentage ratio C1 = ZnO / (CaO+MgO), the range of C1 is 0.417~2.0, the weight percentage ratio C2 = La2O3 / ZnO, the range of C2 is 0.26~1.5; the glass fiber composition does not contain P2O5.

[0061] Preferred Example 9

[0062] The glass fiber composition according to this application contains the following components, the content of each component being expressed as a weight percentage: SiO2 48~56%, B2O3 19.5~27%, Al2O3 10~13%, CaO 0.9~5.0%, MgO 0~2.0%, ZnO 1.5~6.0%, La2O3 0.05~3.5%, Na2O+K2O+Li2O 0.01~0.45%, Fe2O3 0~0.5%, TiO2 0~0.4%;

[0063] Wherein, the sum of the weight percentages of the above components is greater than or equal to 99.3%, the weight percentage ratio C1 = ZnO / (CaO+MgO), the range of C1 is 0.25~2.5, the weight percentage ratio C2 = La2O3 / ZnO, the range of C2 is 0.008~2; the glass fiber composition does not contain P2O5.

[0064] Preferred Example 10

[0065] The glass fiber composition according to this application contains the following components, the content of each component being expressed as a weight percentage: SiO2 48~57%, B2O3 19~29%, Al2O3 10~14%, CaO 0.5~5.0%, MgO 0%, ZnO 0.5~6.0%, La2O3 0.05~4.0%, Na2O+K2O+Li2O 0.01~0.45%, Fe2O3 0%, TiO2 0%, F2O 0~0.5%;

[0066] Wherein, the sum of the weight percentages of the above components is greater than or equal to 99.8%, the weight percentage ratio C1 = ZnO / (CaO+MgO), the range of C1 is 0.25~2.5, the weight percentage ratio C2 = La2O3 / ZnO, the range of C2 is 0.008~2; the glass fiber composition does not contain P2O5.

[0067] This application utilizes a high-temperature electric furnace in a laboratory to melt glass samples. First, various raw materials are prepared into a batch according to the designed formula. After the batch is mixed evenly, it is placed in a high-temperature electric furnace to melt into a uniform glass liquid. The glass liquid is then poured into glass blocks of a specified shape as required, annealed, and after cooling, the glass blocks are cut into glass sheets of a specified shape. Relevant performance parameters are then tested.

[0068] The following basic parameters are selected for testing:

[0069] The dielectric constant and dielectric loss at 10 GHz were determined using the resonant cavity method. The glass required to be melted, annealed, cut and polished during sample preparation.

[0070] The forming temperature corresponds to the temperature at which the glass melt has a viscosity of 103 poise. During sample preparation, the glass block is placed in an alumina crucible, and after heating, the temperature corresponding to the viscosity is measured by controlling the temperature and the viscosity curve; this is the forming temperature.

[0071] Liquidothermal temperature, i.e., the upper limit temperature of glass crystallization and phase separation. During sample preparation, the glass is placed in a clay crucible, and the liquidus temperature is read by observing the temperature distribution of the gradient temperature furnace and the crystallization and phase separation boundary.

[0072] ΔT is the difference between the forming temperature and the liquidus temperature, characterizing the temperature range for glass fiber drawing. A larger ΔT is more beneficial for the operation.

[0073] The above basic parameters and their measurement methods are well known to those skilled in the art and are measured using industry-standard testing methods.

[0074] The performance parameters of the glass fiber compositions of this application in the examples and comparative examples are further compared below by way of a list. The content of each glass fiber composition is expressed as a weight percentage. It should be noted that the total content of the components in the examples is slightly less than 100%, which can be understood as the residual amount being trace impurities or a small amount of components that cannot be analyzed.

[0075] Tables 1-3 list some specific embodiments of this application, numbered S1-S15, and Tables 4-5 show comparative embodiments K1-K9. K1 contains neither ZnO nor La2O3, K2 contains ZnO but not La2O3, K3 contains La2O3 but not ZnO, K4 is a typical E-glass comparative embodiment, K5 is a typical D-glass comparative embodiment, K6-K8 are comparative embodiments containing different proportions of ZnO and La2O3, and K9 is a comparative embodiment containing P2O5. The glass fiber composition in the tables is expressed as a weight percentage.

[0076] Table 1 Formula S1 S2 S3 S4 S5 SiO2 48.0 53.2 57.0 56.0 53.0 B2O3 29.0 23.0 20.0 19.0 24.0 Al2O3 13.0 13.0 13.0 13.0 13.0 CaO 3.0 0.5 3.0 4.0 5.0 MgO 0 1.5 0 2.0 0 ZnO 3.2 5.0 3.2 1.5 1.5 La2O3 3.1 3.1 3.1 3.0 2.8 Na2O + K2O + Li2O 0.2 0.2 0.2 0.2 0.2 Fe2O3 0 0 0 0.5 0 TiO₂ 0 0 0 0.3 0 F2 0.5 0.5 0.5 0.5 0.5 C1 = ZnO / (CaO+MgO) 1.067 2.500 1.067 0.250 0.300 C2=La2O3 / ZnO 0.969 0.620 0.969 2.000 1.867 Dielectric constant at 10 GHz 4.4 4.4 4.3 4.4 4.4 Dielectric loss at 10GHz 0.0019 0.0022 0.0017 0.0026 0.0026 Molding temperature 1361 1377 1380 1362 1335 Liquidus temperature 1265 1312 1269 1278 1201 ΔT 96 65 111 84 134

[0077] Table 2 formula S6 S7 S8 S9 S10 SiO2 54.7 52.0 54.0 54.0 55.25 B2O3 23.0 25.0 23.0 23.0 23.0 Al2O3 13.0 13.0 13.0 13.0 12.0 CaO 3.0 3.0 3.0 3.0 2.0 MgO 0 0 0 0 1.0 ZnO 1.0 3.0 4.0 5.0 6.0 La2O3 4.0 3.3 2.3 1.3 0.05 Na2O+K2O+Li2O 0.2 0.2 0.2 0.2 0.2 Fe2O3 0.3 0 0 0 0 TiO2 0.3 0 0 0 0 F2 0.5 0.5 0.5 0.5 0.5 C1 = ZnO / (CaO+MgO) 0.333 1.000 1.333 1.667 2.000 C2=La2O3 / ZnO 4.000 1.100 0.575 0.260 0.008 Dielectric constant at 10 GHz 4.5 4.4 4.4 4.3 4.3 Dielectric loss at 10GHz 0.0027 0.0022 0.0021 0.0019 0.0020 Molding temperature 1375 1360 1366 1349 1355 Liquidus temperature 1249 1269 1280 1289 1318 ΔT 126 91 86 60 37

[0078] Table 3 formula S11 S12 S13 S14 S15 SiO2 56.0 49.0 54.0 54.59 50.15 B2O3 21.0 27.0 23.0 19.5 26.0 Al2O3 13.0 10.0 14.0 13.0 13.0 CaO 2.9 4.0 0.9 5.0 4.8 MgO 0.1 0 2.0 1.0 0.0 ZnO 3.2 5.3 2.3 3.2 2.0 La2O3 3.1 4.0 3.0 3.1 3.0 Na2O + K2O + Li2O 0.2 0.2 0.2 0.01 0.45 Fe2O3 0 0 0.3 0.3 0.3 TiO2 0 0 0.3 0.3 0.3 F2 0.5 0.5 0.0 0.0 0.0 C1 = ZnO / (CaO+MgO) 1.067 1.325 0.793 0.533 0.417 C2=La2O3 / ZnO 0.969 0.755 1.304 0.969 1.500 Dielectric constant at 10 GHz 4.2 4.3 4.3 4.3 4.3 Dielectric loss at 10GHz 0.0019 0.0020 0.0018 0.0023 0.0026 Molding temperature 1379 1355 1375 1365 1357 Liquidus temperature 1231 1256 1260 1240 1244 ΔT 148 99 115 125 113

[0079] Table 4 formula K1 K2 K3 K4 K5 SiO2 55.5 53.0 54.0 54.2 75.3 B2O3 23.0 23.0 22.9 7.3 19.8 Al2O3 13.0 13.0 13.0 14.3 0.7 CaO 6.0 3.3 4.8 22.3 0.8 MgO 1.8 0 1.6 0.4 0.4 ZnO 0 7.0 0 0 0 La2O3 0 0 3.0 0 0 Na2O + K2O + Li2O 0.2 0.2 0.2 0.6 3.0 Fe2O3 0 0 0 0.2 0 TiO2 0 0 0 0.2 0 F2 0.5 0.5 0.5 0.5 0 C1 = ZnO / (CaO+MgO) 0 2.121 0.0 0 0 C2=La2O3 / ZnO — 0 — — — Dielectric constant at 10 GHz 4.5 4.5 6.4 6.6 4.6 Dielectric loss at 10GHz 0.0027 0.0024 0.0032 0.0065 0.0058 Molding temperature 1335 1332 1332 1175 1415 Liquidus temperature 1070 1302 1080 1070 950 ΔT 265 30 252 105 465

[0080] Table 5 formula K6 K7 K8 K9 SiO2 51.5 53.0 50.6 51.5 B2O3 21.0 27.0 18.9 22.0 Al2O3 13.8 9.0 13.0 13.5 CaO 6.0 3.3 4.8 6.0 MgO 0 0 1.6 0 ZnO 2.0 1.0 6.5 2.0 La2O3 5.0 6.0 3.0 3.0 Na2O + K2O + Li2O 0.2 0.2 0.6 0.2 Fe2O3 0 0 1.0 0.3 TiO2 0 0 0 0.5 F2 0.5 0.5 0 0 P2O5 - - - 1.0 C1=ZnO / (CaO+MgO) 0.333 0.303 1.016 0.333 C2=La2O3 / ZnO 2,500 6.000 0.462 1.500 Dielectric constant at 10 GHz 4.8 Unable to form uniform glass 4.9 4.7 Dielectric loss at 10GHz 0.0031 Unable to form uniform glass 0.0032 0.0030 Molding temperature 1320 Unable to form uniform glass 1295 1341 Liquidus temperature 1100 Unable to form uniform glass 1080 1143 ΔT 220 Unable to form uniform glass 215 198

[0081] The K7 glass formulation cannot form a uniform glass when melted in a high-temperature electric furnace because the Al2O3 content is too low and the network lacks oxygen atoms and groups, which will cause phase separation in the glass.

[0082] As can be seen from Tables 1-5, the glass fiber prepared by the glass fiber composition described in this application has excellent dielectric properties at a high frequency of 10 GHz compared with the comparative embodiments. Specifically, the dielectric constant is ≤4.5 and the dielectric loss is ≤2.7‰. In addition, the glass fiber composition has moderate viscosity and a wide fiber forming range, which is suitable for large-scale tank furnace production.

[0083] Among them, the overall performance of Examples S1, S7-S9, and S12 is superior. Compared with the conventional E glass of the comparative examples, the present application has a lower dielectric constant and dielectric loss; and compared with the conventional D glass, the present application has a better melting effect and is more suitable for large-scale tank furnace production.

[0084] Further analysis of the examples and comparative examples reveals that: based on the general CaO-B2O3-SiO2-Al2O3 glass system, controlling the content of MgO and alkali metals is crucial. Introducing ZnO alone reduces the dielectric loss of the glass, but introduces certain risks to the forming range, leading to a decrease in the ΔT value. Introducing La2O3 alone has little effect on reducing the dielectric constant and dielectric loss of the glass, and may even have adverse effects. However, simultaneously introducing appropriate amounts of ZnO and La2O3 can improve the forming range of the glass while ensuring low dielectric constant and low dielectric loss, and the viscosity temperature is also moderate. Therefore, the formulation has good practicality and can be promoted for mass production in kilns. Furthermore, when Fe2O3, TiO2, and F2 are controlled at certain levels, they have no adverse effects on the dielectric properties, viscosity temperature, and forming range of the glass.

[0085] The glass fiber composition according to this application can be combined with one or more organic and / or inorganic materials to prepare composite materials with excellent performance, such as copper clad laminate (CCL) and printed circuit board (PCB).

[0086] The above description is merely a preferred embodiment of this application and is not intended to limit this application. Various modifications and variations can be made to this application by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this application should be included within the protection scope of this application.

[0087] The above embodiments are only used to illustrate the technical solutions of this application, and are not intended to limit it. Although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of this application. [Simplified Explanation of the Diagram]

[0088] None.

Claims

1. A glass fiber composition comprising the following components, the content of each component expressed as a weight percentage as follows: SiO2 48~57% B2O3 19~29% Al2O3 10~14% CaO 0.5~5.0% MgO 0~2.0% ZnO 0.5~6.0% La2O3 0.05~4.0% Na2O+K2O+Li2O 0.01~0.45% Fe2O3 0~0.5%; wherein, The total weight percentage of the above components is greater than or equal to 99.0%; the weight percentage ratio C1 = ZnO / (CaO+MgO), with a value of 0.25~2.5, and the weight percentage ratio C2 = La2O3 / ZnO, with a value of 0.008~4.

2. The glass fiber composition as claimed in claim 1, wherein, The glass fiber composition further comprises TiO2, wherein the weight percentage content of TiO2 ranges from 0 to 0.4%.

3. The glass fiber composition as claimed in claim 1, wherein, The glass fiber composition further comprises F2, the weight percentage of which ranges from 0 to 1.6%; the total weight percentage of SiO2, B2O3, Al2O3, CaO, MgO, ZnO, La2O3, Na2O, K2O, Li2O, Fe2O3, and F2 is greater than or equal to 99.3%.

4. The glass fiber composition as claimed in claim 1, wherein, The weight percentage ratio C1 = ZnO / (CaO+MgO) ranges from 0.25 to 2.

3.

5. The glass fiber composition as claimed in claim 1, wherein, The weight percentage ratio C2=La2O3 / ZnO ranges from 0.008 to 2.

6. The glass fiber composition as claimed in claim 1, wherein, The glass fiber composition contains the following components, the content of each component being expressed as a weight percentage as follows: SiO2 48~57% B2O3 19.5~27% Al2O3 10~14% CaO 0.9~5.0% MgO 0~2.0% ZnO 1.5~6.0% La2O3 0.05~3.5% Na2O+K2O+Li2O 0.01~0.45% Fe2O3 0~0.5% TiO2 0~0.4% F2 0.1~1.5%; The total weight percentage of SiO2, B2O3, Al2O3, CaO, MgO, ZnO, La2O3, Na2O, K2O, Li2O, Fe2O3, TiO2, and F2 is greater than or equal to 99.3%; the weight percentage ratio C1 = ZnO / (CaO+MgO), with C1 ranging from 0.25 to 2.5, and the weight percentage ratio C2 = La2O3 / ZnO, with C2 ranging from 0.008 to 2.

7. The glass fiber composition as claimed in claim 1, wherein, The glass fiber composition contains the following components, the content of each component expressed as a weight percentage as follows: SiO2 48~56% B2O3 19.5~27% Al2O3 10~14% CaO 0.9~4.0% MgO 0~2.0% ZnO 1.5~6.0% La2O3 0.05~3.5% Na2O+K2O+Li2O 0.01~0.45% Fe2O3 0~0.5%; wherein, the sum of the weight percentages of the above components is greater than or equal to 99.2%, the weight percentage ratio C1=ZnO / (CaO+MgO), the range of C1 is 0.25~2.5, and the weight percentage ratio C2=La2O3 / ZnO, the range of C2 is 0.008~2.

8. The glass fiber composition as claimed in claim 1, wherein, The glass fiber composition contains the following components, the content of each component being expressed as a weight percentage as follows: SiO2 48~56% B2O3 19.5~27% Al2O3 10~14% CaO 0.9~4.0% MgO 0~2.0% ZnO 1.5~6.0% La2O3 1.3~4.0% Na2O+K2O+Li2O 0.01~0.30% Fe2O3 0~0.5% TiO2 0~0.4% F2 0~1.5%; The total weight percentage of SiO2, B2O3, Al2O3, CaO, MgO, ZnO, La2O3, Na2O, K2O, Li2O, Fe2O3, TiO2, and F2 is greater than or equal to 99.3%; the weight percentage ratio C1 = ZnO / (CaO+MgO), with C1 ranging from 0.25 to 2.5, and the weight percentage ratio C2 = La2O3 / ZnO, with C2 ranging from 0.008 to 2.

9. The glass fiber composition as claimed in claim 1, wherein, The glass fiber composition contains the following components, the content of each component expressed as a weight percentage as follows: SiO2 48~54% B2O3 21~26% Al2O3 10~14% CaO 2.0~4.0% MgO 0~2.0% ZnO 1.5~5.5% La2O3 1.3~4.0% Na2O+K2O+Li2O 0.01~0.25% Fe2O3 0~0.5% TiO2 0~0.4% F2 0~0.5%; wherein, the weight percentage ratio C1=ZnO / (CaO+MgO), C1 ranges from 0.25 to 2.5, and the weight percentage ratio C2=La2O3 / ZnO, C2 ranges from 0.008 to 2.

10. The glass fiber composition as claimed in claim 1, wherein, The glass fiber composition does not contain P2O5.

11. A glass fiber made from a glass fiber composition as described in any one of claims 1 to 10.

12. A composite material comprising glass fiber as described in claim 11.